2012
DOI: 10.1038/onc.2012.552
|View full text |Cite
|
Sign up to set email alerts
|

Targeting genetic alterations in protein methyltransferases for personalized cancer therapeutics

Abstract: The human protein methyltransferases (PMTs) constitute a large enzyme class composed of two families, the protein lysine methyltransferases (PKMTs) and the protein arginine methyltransferases (PRMTs). Examples have been reported of both PKMTs and PRMTs that are genetically altered in specific human cancers, and in several cases these alterations have been demonstrated to confer a unique dependence of the cancer cells on PMT enzymatic activity for the tumorigenic phenotype. Examples of such driver alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 68 publications
(94 reference statements)
0
59
0
Order By: Relevance
“…Cancer genomic sequencing campaigns have led to the identification of recurrent genomic abnormalities in genes that encode for chromatin-modifying enzymes (2)(3)(4)(5)(6), supporting the concept that cancer cells utilize the manipulation of chromatin structure as one means to invoke transcriptional programs that prevent differentiation and promote proliferation. The emergence of individual KMTs and KDMs as candidate oncology targets has spurred significant drug discovery efforts with the goal to identify small-molecule inhibitors of these enzymes for cancer therapeutic applications (1,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer genomic sequencing campaigns have led to the identification of recurrent genomic abnormalities in genes that encode for chromatin-modifying enzymes (2)(3)(4)(5)(6), supporting the concept that cancer cells utilize the manipulation of chromatin structure as one means to invoke transcriptional programs that prevent differentiation and promote proliferation. The emergence of individual KMTs and KDMs as candidate oncology targets has spurred significant drug discovery efforts with the goal to identify small-molecule inhibitors of these enzymes for cancer therapeutic applications (1,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of histone methylation can result in reprogramming of gene expression networks and has been associated with diverse disease states, including cancer (4,5,7). Accordingly, enzymes regulating lysine methylation have emerged as a group of promising drug targets (7,10,11).…”
mentioning
confidence: 99%
“…The PMTs constitute an interesting target class for cancer therapeutics both because of the critical role these enzymes play in controlling cellular programs of gene transcription and because, increasingly, bioinformatic surveillance of cancer genome databases are showing that a number of these enzymes are implicated in specific human cancers (5,8); in a recent review, for example, Copeland listed over 10 PMTs for which genetic alterations are found in specific human cancers (8).…”
Section: Introductionmentioning
confidence: 99%
“…Among these various histone modifications (Fig. 1A), methylation of lysine and arginine residues seems to play a particularly important role in control of gene transcription programs (3)(4)(5). These modifications are catalyzed by a class of group-transfer enzymes known as the protein methyltransferases (PMT; refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation